2015
DOI: 10.1007/s10585-015-9726-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous lung and lymph node metastasis in transgenic breast cancer is independent of the urokinase receptor uPAR

Abstract: Urokinase-type plasminogen activator (uPA) is an extracellular protease that plays a pivotal role in tumor progression. uPA activity is spatially restricted by its anchorage to high-affinity uPA receptors (uPAR) at the cell surface. High tumor tissue expression of uPA and uPAR is associated with poor prognosis in lung, breast, and colon cancer patients in clinical studies. Genetic deficiency of uPA leads to a significant reduction in metastases in the murine transgenic MMTV-PyMT breast cancer model, demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…uPAR overexpression is associated with an increased propensity for cancer progression and metastasis, and thus it has emerged as a promising novel target for the treatment of cancer (17). Previous studies indicated that intact uPAR and its cleaved forms are associated with the process of tumor initiation (18) and metastasis (19). Results of the study by Margheri et al (20) indicated that silencing of uPAR altered the metastatic characteristics of advanced cancer; however, to the best of our knowledge, the mechanism underlying the role of uPAR in OTSCC invasion and migration has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…uPAR overexpression is associated with an increased propensity for cancer progression and metastasis, and thus it has emerged as a promising novel target for the treatment of cancer (17). Previous studies indicated that intact uPAR and its cleaved forms are associated with the process of tumor initiation (18) and metastasis (19). Results of the study by Margheri et al (20) indicated that silencing of uPAR altered the metastatic characteristics of advanced cancer; however, to the best of our knowledge, the mechanism underlying the role of uPAR in OTSCC invasion and migration has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…In general, pathologies associated with chronic inflammation, such as rheumatoid arthritis, cancer, and Crohn’s disease, display elevated uPAR expression levels at their lesion sites primarily due to infiltrating immune cells. While evidence for a direct causal effect of uPAR-expression on disease progression often remains uncertain ( Almholt et al, 2015 ), elevated uPAR levels in resected lesions or shed into the circulation are strong and robust surrogate biomarkers of disease severity. Most observational studies find an inverse correlation between elevated plasma levels of soluble uPAR and patient performance and survival ( Lund et al, 2011 ; Madunic, 2018 ).…”
Section: Upar Biologymentioning
confidence: 99%
“…Although impairment of uPAR function or inhibition of its expression was associated with impaired invasive, metastatic, and tumorigenic potential of many tumor models in vitro and in vivo [ 4 , 11 , 12 , 14 , 16 , 17 , 20 , 52 , 57 , 79 , 84 , 85 ], one study in transgenic mice with uPAR gene ablation showed no pronounced causal effects on disease dissemination by metastasis [ 86 ].…”
Section: Biology Of the Urokinase Receptormentioning
confidence: 99%